Deviation of Faith in Malaysia: An Analysis (International Journal of Environmental Sciences, 2025)
The main objective of this paper is to analyse the issues on deviation of faith in Malaysia. The problem relating to deviation of faith needs to be urgently addressed as it directly affects Islamic theology and Muslims. Although Malaysia has witnessed a rapid development in the field of Islamic understanding and da‘wah missionary among the Muslim community, the heretic movement is still rampant. This scenario has raised questions on factors that contribute to the movement of deviation of faith among the Muslim community. These questions encourage the researcher into researching the subject in order to come forward with answers and solutions. In order to arrive at the answers, the researcher has conducted a research by adopting two research methods namely library research and field work research. For library research, past literature and relevant views about the issue of cultism were collected. The field work research involves observations and surveys is done through interviews. The facts and relevant information are obtained directly from the people concerned and also from the current situations of Muslim society. All data is analysed inductively and deductively to expose the important factors that contribute to the movement of deviation of faith in Malaysia, as well as the solutions and actions taken to combat this problem successfully. The result of this research proves that there are seven factors which contribute to the development of deviation of faith in Malaysia. They are the weakness of enforcement of law, the weakness of Islamic studies curriculum, the influences of western culture, negative contents in mass media, ancient belief, the characteristic of the cults and the weakening of Islamic values.